Selective silicate-directed motility in diatoms - Karen Grace V. Bondoc (Nature Portfolio, 2016)
Diatoms often dominate production in aquatic communities, but the amount of available dissolved silicic acid (dSi) limits their growth. Here, Bondoc et al., show that diatoms perceive gradients in dSi, and can increase the encounter with this resource by chemotaxis toward high concentrations under resource-limited conditions.